Resilience Under Pressure: Investigating the Relationship Between Self-Efficacy, Self-Esteem, and Stress - Fitri Astutik; Wahyu Eko Pujianto (Universitas Islam Negeri (UIN) Salatiga, 2025)
This This study aims to examine the relationship between self-efficacy, self-esteem, resilience, and stress in final semester students. Using a quantitative approach, data were collected through a questionnaire distributed to 160 final semester students in Surabaya and Sidoarjo. Data analysis was carried out using Smart PLS4 to test the validity, reliability, and relationships between variables. The results showed that self-efficacy and self-esteem had a significant negative effect on stress when reinforced by resilience, while resilience itself played an important role in reducing stress levels. These findings emphasize the importance of development interventions aimed at improving self-efficacy, self-esteem, and resilience to help final semester students manage academic stress and life transitions, and improve their psychological well-being.